Hierarchical simulations of diffusion in zeolites - Papadopoulos, George K.; Theodorou, Doros N. (Diffusion Fundamentals, 2005)
The work presented in this chapter involves comparison of simulation and experimental results for intracrystalline and long-range diffusion in zeolitic media in order to demonstrate the hierarchical character of the study of transport in microporous structures in response to the need to address sorption and diffusion phenomena in porous materials over broad scales of length and time.